2022
DOI: 10.3390/ijms23179910
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vemurafenib-Resistant Melanoma Cell Lines Reveals Novel Hallmarks of Targeted Therapy Resistance

Abstract: Regardless of the significant improvements in treatment of melanoma, the majority of patients develop resistance whose mechanisms are still not completely understood. Hence, we generated and characterized two melanoma-derived cell lines, primary WM793B and metastatic A375M, with acquired resistance to the RAF inhibitor vemurafenib. The morphology of the resistant primary WM793B melanoma cells showed EMT-like features and exhibited a hybrid phenotype with both epithelial and mesenchymal characteristics. Surpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…In vitro observation of the involvement of ezrin in vemurafenib resistance in BRAFV600E-mutated RKO colon cancer cells prompted us to examine whether ezrin plays an important role in acquired resistance to BRAFV600E inhibition in another BRAFV600E-mutated cancer such as melanoma. Previous literature data already provide an evidence of the role of the actin cytoskeleton in mediating adaptive resistance to vemurafenib in BRAFV600E-mutant melanoma cells [ 20 , 21 ]. Knowing that ezrin is involved in the regulation of the actin cytoskeleton organisation, we analysed the expression levels of total ezrin and phospho-ezrin (T567) in vemurafenib-sensitive and vemurafenib-resistant A375 melanoma cells harbouring the BRAFV600E mutation under the baseline culture conditions and after exposure to 0.8 µM vemurafenib (corresponding to the IC50 concentration of vemurafenib measured in sensitive melanoma cells) for 72 h ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro observation of the involvement of ezrin in vemurafenib resistance in BRAFV600E-mutated RKO colon cancer cells prompted us to examine whether ezrin plays an important role in acquired resistance to BRAFV600E inhibition in another BRAFV600E-mutated cancer such as melanoma. Previous literature data already provide an evidence of the role of the actin cytoskeleton in mediating adaptive resistance to vemurafenib in BRAFV600E-mutant melanoma cells [ 20 , 21 ]. Knowing that ezrin is involved in the regulation of the actin cytoskeleton organisation, we analysed the expression levels of total ezrin and phospho-ezrin (T567) in vemurafenib-sensitive and vemurafenib-resistant A375 melanoma cells harbouring the BRAFV600E mutation under the baseline culture conditions and after exposure to 0.8 µM vemurafenib (corresponding to the IC50 concentration of vemurafenib measured in sensitive melanoma cells) for 72 h ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, reduced levels of TAp73 and ∆Np73 were observed in BRAFi-resistant primary melanoma cells with the activation of the PI3K/AKT pathway, while increased levels of TAp73 and ∆Np73 were detected in resistant metastatic melanoma cells with the re-activation of the MAPK pathway [79]. The BRAFi-resistant primary melanoma cells show features of slow-cycling cells, e.g., mesenchymal morphology, reduced proliferation and migration, increased resistance to chemotherapeutic agents, i.e., cisplatin and etoposide, as well as altered cell cycle profile and levels of cell cycle regulators [106], implying that the specific p53 isoform expression pattern could correlate with specific features of BRAFi-resistant melanoma cells. Interestingly, the slow-cycling cell phenotype, known to be a feature of a targeted therapy-resistant melanoma cells [28,106], can be prevented by the inhibition of p53, thus sensitizing melanoma cells to BRAFi/MEKitargeted therapy [28].…”
Section: The Role Of P53 Family Isoforms In Resistance To Targeted Th...mentioning
confidence: 99%
“…The BRAFi-resistant primary melanoma cells show features of slow-cycling cells, e.g., mesenchymal morphology, reduced proliferation and migration, increased resistance to chemotherapeutic agents, i.e., cisplatin and etoposide, as well as altered cell cycle profile and levels of cell cycle regulators [106], implying that the specific p53 isoform expression pattern could correlate with specific features of BRAFi-resistant melanoma cells. Interestingly, the slow-cycling cell phenotype, known to be a feature of a targeted therapy-resistant melanoma cells [28,106], can be prevented by the inhibition of p53, thus sensitizing melanoma cells to BRAFi/MEKitargeted therapy [28]. In more detail, it has been shown that the slow-cycling phenotype is driven by non-canonical Wnt signaling via the Wnt5A protein, which stabilizes and utilizes p53.…”
Section: The Role Of P53 Family Isoforms In Resistance To Targeted Th...mentioning
confidence: 99%
“…Pre-clinical studies carried out in cell lines with primary or acquired resistance as model systems have enabled the dissection of molecular mechanisms that act by sustaining MAPK signaling or parallel signaling networks despite BRAF inhibition. In vitro studies identified different epigenetic, metabolic, and phenotypic reprogramming events associated to resistance, contributing to the definition of the heterogeneous alterations associated with the reactivation of MAPK signaling ( 21 ). In addition, these model systems represent a tool to develop novel drug combinations to improve precision medicine strategies.…”
Section: Introductionmentioning
confidence: 99%